The relationship between subchondral sclerosis detected with MRI and cartilage loss in a cohort of subjects with knee pain: the knee osteoarthritis progression (KOAP) study - Crema, M. D.; Cibere, J.; Sayre, E. C.; Roemer, Frank; Wong, H.; Thorne, A.; Singer, J.; Esdaile, J. M.; Marra, M. D.; Kopec, J. A.; Nicolaou, S.; Guermazi, A. (Osteoarthritis and Cartilage, 2014)
To assess the association between subchondral sclerosis detected at baseline with MRI and cartilage loss over time in the same region of the knee in a cohort of subjects with knee pain.163 subjects with knee pain participated in a longitudinal study to assess knee osteoarthritis progression (KOAP). Subjects received baseline knee radiographs as well as baseline and 3-year follow-up MRI examinations. Baseline subchondral sclerosis and bone marrow lesions (BMLs) were scored semiquantitatively on MRI in each region from 0 to 3. Cartilage morphology at baseline and follow-up was scored semiquantitatively from 0 to 4. The association between baseline subchondral sclerosis and cartilage loss in the same region of the knee was evaluated using logistic regression, adjusting the results for age, gender, body mass index, and the presence of concomitant BMLs.The prevalence of subchondral sclerosis detected by MRI in the regions of the knee varied between 1.6% (trochlea) and 17% (medial tibia). The occurrence of cartilage loss over time in regions varied between 6% (lateral tibia) and 13.1% (medial femur). The prevalence of radiographically-detected subchondral sclerosis in compartments varied from 2.9% (patellofemoral) to 14.2% (medial tibiofemoral). In logistic regression models, there were no significant associations between baseline subchondral sclerosis detected by MRI and cartilage loss in the same region of the knee.Baseline subchondral sclerosis as detected by MRI did not increase the risk of cartilage loss over time.
EVALuna2:14457